Evaluation of Job Preference of Prospective Dentists using Discrete Choice Experiment - Shrestha, Rabindra Man; Shrestha, Sujita; Sapkota, Vishnu Prasad (Economic Journal of Development Issues, 2017)
Introduction: The number of dentists is increasing in Nepal and they have a tendency to accumulate in the capital and major cities of the country. Moreover, their job priorities and professional inclinations have not been identified yet. The need, demand and supply of the dental professionals and their retention in rural areas are required to be studied from the health economics perspective. The main objective of the study was to identify preferences on job characteristics of prospective dentists and determine monetary valuation of the attributes of job choices. Methodology: Discrete choice experiment (DCE) with choice sets in the form of self-administered questionnaire was used. 402 Nepalese dental students, interns and recently graduated dentists from various universities were studied. Seven job characteristics and their corresponding levels were determined from focus group discussion. We adopted main effect fractional factorial design to create 48 choice sets. The respondents were divided into 6 blocks, with each block comprising of 8 choice sets. Each choice set comprised of two choices and an alternative specific constant (ASC). Multiple logistic regression with mixed logit model was applied to analyze the preferences of various job characteristics. Results: The response rate was 74%. Further educational opportunity was the most important job attribute for dentists in choosing their job. The order of preference for other job characteristics was: amenities at workplace, distance to workplace, private practice opportunity, and additional incentive. (p<0.01). Whereas, the job attribute CPD opportunity was not found statistically significant and has negative estimated coefficient. The ‘willingness-to-accept’ was found maximum (NRs. 144,000) for educational opportunity. (p/a). The preferences varied with gender, location and respondent category. Conclusion: Job characteristics like further education opportunity and amenities at workplace should be given importance in creating job opportunities for dentists. The offering of preferred job attributes could be helpful in retaining the dental professionals in rural areas. Economic Journal of Development Issues Vol. 19 & 20 No. 1-2 (2015) Combined Issue, Page: 100-119